Development and Validation of an Objective Scoring Tool to Evaluate Surgical Dissection: Dissection Assessment for Robotic Technique (DART). Issue 5 (25th September 2021) - Vanstrum, Erik B.; Ma, Runzhuo; Maya-Silva, Jacqueline; Sanford, Daniel; Nguyen, Jessica H.; Lei, Xiaomeng; Chevinksy, Michael; Ghoreifi, Alireza; Han, Jullet; Polotti, Charles F.; Powers, Ryan; Yip, Wesley; et al.
Abstract: Introduction: Evaluation of surgical competency has important implications for training new surgeons, accreditation, and improving patient outcomes. A method to specifically evaluate dissection performance does not yet exist. This project aimed to design a tool to assess surgical dissection quality. Methods: Delphi method was used to validate structure and content of the dissection evaluation. A multi-institutional and multi-disciplinary panel of 14 expert surgeons systematically evaluated each element of the dissection tool. Ten blinded reviewers evaluated 46 de-identified videos of pelvic lymph node and seminal vesicle dissections during the robot-assisted radical prostatectomy. Inter-rater variability was calculated using prevalence-adjusted and bias-adjusted kappa. The area under the curve from receiver operating characteristic curve was used to assess discrimination power for overall Dissection Assessment for Robotic Technique (DART) scores as well as domains in discriminating trainees (≤100 robotic cases) from experts (>100). Results: Four rounds of Delphi method achieved language and content validity in 27/28 elements. Use of 3 or 5-point scale remained contested; thus, both scales were evaluated during validation. The 3-point scale showed improved kappa for each domain. Experts demonstrated significantly greater total scores on both scales (3-point, p <0.001; 5-point, p <0.001). The ability to distinguish experience was equivalent for total score on both scales (3-point AUC=0.92, CI 0.82–1.00; 5-point AUC=0.92, CI 0.83–1.00). Conclusions: We present the development and validation of DART, an objective and reproducible 3-point surgical assessment to evaluate tissue dissection. DART can effectively differentiate levels of surgeon experience and can be used in multiple surgical steps.